Circular economy valorization of oyster shell waste for biological control of Aedes aegypti mosquito larvae - Taddao Pahasup-Anan; Bhuvaneswari Kandasamy; Rotruedee Chotigawin; Pitsanu Pannaracha; Teeranun Nakyai; Mayurin Laorujisawat; Surachai Wongcharee; Kowit Suwannahong (Environmental Challenges)
Dengue fever, caused by the dengue virus and transmitted primarily by Aedes aegypti mosquitoes, remains a significant health threat in tropical and subtropical regions. In Thailand, particularly in Thap Ma Municipality, Rayong Province, the incidence of dengue fever remains alarmingly high, necessitating the development of effective and sustainable mosquito control strategies. This study examines the valorization of oyster shell waste, a plentiful marine by product, as a sustainable larvicide alternative as a green mosquito repellent to conventional chemical mosquito repellent, such as organophosphate-based Abate. Aligned with circular economy principles, the research involved collaboration with the Thap Ma community to develop and evaluate mosquito larvae elimination products derived from treated oyster shells. Four formulations were tested, with Formula 1 (without herbal additives) and Formula 4 (with turmeric) demonstrating the highest potential due to their simplicity, ease of use, and larvicidal efficacy. Environmental and socio-economic assessments revealed promising outcomes, including an eco-efficiency score of 666.67, a Social Return on Investment (SROI) of 19.53, and an estimated reduction in greenhouse gas emissions of 0.0143 tons CO2-equivalent per year. These findings support the development of oyster shell-based larvicides as a green mosquito repellent, an eco-friendly, community-driven solution to vector control.